Generation of the First TCR Transgenic Mouse with CD4+ T Cells Recognizing an Anti-inflammatory Regulatory T Cell-Inducing Hsp70 Peptide - Jansen, Manon A. A.; van Herwijnen, Martijn J. C.; van Kooten, Peter J. S.; Hoek, Aad; van der Zee, Ruurd; van Eden, Willem; Broere, Femke (Frontiers in Immunology, 2016)
Antigen-specific regulatory T cells (Tregs) directed at self-antigens are difficult to study since suitable specific tools to isolate and characterize these cells are lacking. A T cell receptor (TCR)-transgenic mouse would generate possibilities to study such antigen-specific T cells. As was shown previously, immunization with the mycobacterial heat shock protein 70 derived peptide B29 and its mouse homologues mB29a and mB29b induced anti-inflammatory responses. Furthermore, B29 induced antigen-specific regulatory T cells (Tregs) in vivo. To study mB29b specific Tregs, we isolated the TCR from T cell hybridomas generated against mB29b and produced a TCR transgenic mouse that expresses a MHC-class II restricted mB29b-specific TCR. These TCR transgenic CD4+ T cells were found to cross react with the B29 epitope as identified with peptide induced proliferation and IL-2 production. Thus, we have successfully generated a novel mouse model with antigen-specific CD4+ T cells that recognize self and bacterial heat shock protein (Hsp) 70 derived peptides. With this novel mouse model, it will be possible to study primary antigen specific T cells with specificity for a regulatory HSP70 T cell epitope. This will enable the isolation and characterization CD4+CD25+ Tregs with a proven specificity. This will provide useful knowledge of the induction, activation and mode of action of Hsp70- specific Tregs, for instance during experimental arthritis.